Combined Effect of Noise and Smoking on the Cognitive Performance of Automotive Industry Workers - Iraj Alimohammadi; Fakhradin Ahmadi kanrash; Jamileh Abolaghasemi; Ali Shahbazi; Hanieh Afrazandehh; Kazem Rahmani (Basic and Clinical Neuroscience, 2019)
Introduction: Noise is an environmental stressor and can cause or exacerbate mental disorders, and affect the individual performance in certain conditions. This study aimed to evaluate the combined effects of noise and smoking on the cognitive performance of the workers in the automotive industry. Methods: This research is a descriptive-analytical study with a cross-sectional design conducted on 300 workers randomly assigned into two groups of noise-exposed and nonexposed. They were examined using computerized tests, including the Tower of London test (TOL), Continuous Performance test (CPT), and Stroop test. The sound pressure levels were measured based on an 8-hour equal-loudness contour in each group according to ISO 9612 standard, using the Testo CEL-815 sound level meter. Results: The study of combined effects of noise and smoking on 12 CPT indicators using the 2-way Analysis of Variance (ANOVA) indicate that noise and smoking factors had a significant impact on the mean number of errors and correct responses in the third 50-stimuli stage, the mean number of errors and correct responses in the second 50-stimuli stage with P<0.001, P<0.001, P=0.012 and P<0.001 for smoking respectively, but only noise affected the other 7 indicators (P<0.001). Conclusion: Smoking and noise have negative impacts on concentration, attention, and cognitive processing speed, which can lead to an individual’s mistakes and delayed decision making at the workplace.